BIOCHEMISTRY STUDIES IN BLOOD AND BODY FLUIDS OF TUBERCULAR PATIENTS - Syed Shabbar Masih (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: One of the oldest diseases known to impact humans, tuberculosis is a leading cause of death in the entire world. The lungs are typically affected by this condition, which is brought on by bacteria from the Mycobacterium TB complex, though other organs may also be involved in up to one-third of cases. TB caused by drug-susceptible strains is almost always curable if properly treated. In 50–65% of instances, the condition may be deadly if left untreated within 5 years. Typically, infected pulmonary TB patients create droplet nuclei that are disseminated through the air by other patients. According to the WHO study "TB in the South-east Asia Area," India reported 1.9 million new cases in 2006. 9.2 million new TB cases were reported globally during this time. HIV infection affected 1.2 percent of all new cases in the nation, and multi-drug resistant TB affected 2.8 percent of all new cases (MOR-TB). A strong index of suspicion is essential for the diagnosis of tuberculosis. Aim: The aim of the present study is Biochemistry studies in blood and body fluids of tubercular patients. Evaluation and significance of ADA activity and CRP in blood and body fluids of tubercular patients. Material and Method: The present study "Biochemical Studies in Blood and Body Fluids of Tubercular Patients" was carried out in Department of Biochemistry. The cases under study included pulmonary and other sites tuberculosis, non-tubercular disease cases and age &sex matched healthy controls. A total of 50 real cases of pulmonary tuberculosis were chosen for the study in group B, along with 50 instances of unrelated illnesses in group C and 50 healthy, age- and sex-matched controls in group A. The controls and study group’s blood was drawn via venipuncture, transferred to an EDTA vacutainer, utilised for haematological testing, and serum was used for the examination of ADA, CRP, and IFN-γ. Results: Conventional markers of TB i.e., serum ADA and serum CRP levels are significantly higher in tuberculous patients as compared with the healthy age & sex matched controls and other non-tubercular disease cases. The levels of new markers, serum IFN-γ found to be significantly higher in TB patients compared to non-tubercular cases and healthy control included in the study. The levels of serum ADA and serum CRP were also found to be higher in various body fluids in those suffering with tuberculosis compared to that with non-tubercular diseases associated fluid accumulation. It is also concluded that there is significant positive co-relation between bacterial positivity and body fluid ADA and CRP levels. Similarly, there is also significant positive co-relation observed between serum ADA and serum CRP levels between tubercular and non- tubercular cases Conclusion: Based on the findings of the current study, it can be deduced that iron deficiency anaemia is linked to the production of free radicals, anomalies, and peroxidation of essential body molecules, increasing the danger for both pregnant women and the developing baby. To evaluate the status of antioxidant in pregnancy-related disorder, more extensive research is required. During a diabetic pregnancy, gestational diabetes causes an oxidative stress situation that makes membrane damage and lipoperoxidability easier to occur. Keywords: Adenosine deaminase, Anti-diuretic Hormone, Bacillus Calmette Guerin, Cerebrospinal fluid and Interferon gamma